Os gastos públicos em educação e a variação da proficiência: uma análise do período 2005-2007 - Becker, Fernanda da Rosa (2009)
This study aimed at the public expenses in education and its impact on the level of the student's proficiency. The data passed through a statistical and an econometrical analysis. The multiple regressions did not identify a significant relation between the differential of expenses per pupil in the elementary level and the level of proficiency of the students of municipal schools. It is possible to conclude that a raise of the level of resources isolated cannot contribute to the improvement of the system. The quality of the public expenses must be monitored in order to promote more effective polices.